CHARTERED PUBLIC ACCOUNTÂ´S PERCEPTION ON MATERIALITY - Maqellari, Majlinda; Dika, Ines (European Scientific Journal, ESJ, 2015)
In this paper we want to bring out how the Albanian CPA65, according to his/her professional judgment on financial statements, his/her experience and also the procedures of risk determination, can calculate the materiality and perform substantive tests. In determining what â€œmaterialityâ€ refers to, i.e. in a financial audit, the auditor, based on his/her professional judgment, must decide which items are materials. The auditors must go beyond a numerical calculation of materiality and risk, their experience over the years as auditors, the experience of audited companies or the experience in the same field. Personal judgment does not mean that the auditor can reach or form conclusions on his/her own. The auditor always makes conclusions based on the facts which are known to him/her.